Avaliação da política de incentivos fiscais no desenvolvimento econômico do município de Horizonte/Ceará, no período de 2010 a 2020 - Torres, Sanzio Rocha (2024)
This work aims to evaluate the effects on economic development in the municipality of Horizonte, in the state of Ceará, resulting from the tax incentive policy adopted by the municipality during the period from 2010 to 2020. The municipality stands out as having one of the highest GDPs in Ceará (IPECE, 2020), being an important industrial hub in the state and a significant source of revenue from the Tax on the Circulation of Goods and Services (ICMS). Methodologically, the research is descriptive, considering the need for bibliographic and documental review, as well as other procedures such as semi-structured interviews with the institutional authors of the policy. To achieve greater specificity in its results, a qualitative approach was adopted as an alternative to analyze the main effects that the granted incentives had on local economic development. The sources used were the Ceará State Treasury, Horizonte City Hall, Brazilian Institute of Geography and Statistics, Ministry of Labor and Employment, Ceará State Court of Accounts, and the Ceará Institute of Economic Research and Strategy (IPECE). The research observed positive impacts on the municipality's finances, positioning it prominently at the state level. It was noted that incentivized companies contributed significantly to the employed workforce in the municipality, with no observed wage degradation. Thus, it is inferred that the attraction of companies led to an increase in industrial activity, although there was also a decrease in the municipal GDP and a reduction in ICMS revenue.